SCHOOLCHILDREN IMAGINARY FACING PHYSICAL ACTIVITY (Fiep Bulletin - online, 2016)
Social imaginary in school childrenabout physical activityare strongly influencedbysocioeconomic, cultural and media factors which have a big control over high rates ofphysical inactivityandthesehavederived among others, health problems. The research presented in this document had as a principal objective to characterize social imaginary about physical activity in a group of students in the Alfonso Reyes Echandia School in Bogota D.C. - Colombia. The research was based on a qualitative approach case study.  It was developed with three gathering information techniques and different data sources through triangulation in order to do its analysis.  34 teenagers were involved in this project, they were between their 14's and 18's, (median age 15 years DS 1.1), 44% were women and 56% were men.  Data gathering was done inside the school during the classes. The results showed that social imaginary about physical education are based on an institutionalized, centralized and biological aspects. It was also showed that the most dynamic spaces for physical activity are the school and the group of friends. . It has been concluded that playful and socialization are the most important referents in the school process related to physical activity and it is also necessary to include familiar participation and the government in the promotion of that sport practices.
Keywords: social imaginary; physical activity; schoolchildren.